Human rights and access to bioethics education for graduation and post-graduation in physical education - Waltrick, Luciana Teixeira; Marinho, Alcyane (Brazilian journal of physical education and sport, 2021)
This theoretical essay aims to: 1) demonstrate the importance of teaching Bioethics to professionals in the field of Physical Education; (2) defend the teaching of Bioethics in undergraduate and graduate courses in Physical Education; and (3) to present Bioethics with a Latin American focus as a proposal to analyze Human Rights in Brazil in the context of Physical Education. For this, we understand the theoretical essay as a presentation of a reflective and interpretive nature, of a personal judgment of the researchers themselves, based on the existing scientific literature on the topic addressed. Bioethics associated with Human Movement Sciences, high-performance sports, physical activity, and health brings up complex issues such as body image, anorexia, the vulnerability of the professional athlete and bioethical conflicts involved in the relationship between the professional athlete and the professional health care, early sports initiation, in addition to the importance of the physical education professional as an educational agent inserted in public policies for a society that is sedentary and stigmatized. Because of the approximations of bioethical conflicts that technological advances promote in health professions, there is a need to discuss the importance of teaching Bioethics in the academic training of health professionals and, thus, prepare them to reflect on the possible ethical conflicts they will encounter during their professional practice. These, in turn, have a deep and complex relationship with human rights.